Effect of an anti-human Co-029/tspan8 mouse monoclonal antibody on tumor growth in a nude mouse model - Ailane, Naouel; Greco, Céline; Zhu, Yingying; Sala-Valdés, Monica; Billard, Martine; Casal, Ibrahim; Bawa, Olivia; Opolon, Paule; Rubinstein, Eric; Boucheix, Claude (Frontiers in Physiology, 2014)
New therapeutic agents are needed in digestive tract tumours. Co-029/tspan8 is a tetraspanin frequently expressed on human colorectal tumours, In this work, we report the effects of the monoclonal antibody Ts29.2, targeting Co-029/tspan8, on colorectal tumor cells in vitro and after implantation in nude mice. HT29, Isreco1 and SW480 colorectal tumor cell lines were used for this study. HT29 has a strong endogenous expression of Co-029/tspan8, whereas Isreco1 cells don’t express Co-029/tspan8 and SW480 has only a weak expression. Isreco1 and SW480 were transduced to express Co-029/tspan8 at the same level as HT29. In order to check the specificity of the effect of monoclonal antibody Ts29.2, low Co029/tspan8 expressing SW480 cells were injected simultaneously with transduced cells in the back, on the left and right sides of the mice. With an early treatment, Ts29.2 mAb inhibited growth of tumors expressing Co-029/tspan8 up to 70%, whereas a delayed treatment was less efficient. No effect of the antibody on cell proliferation or apoptosis induction was detected in vitro. No increase of activated caspase 3 labeling was observed in vivo and areas occupied by vessels were not significantly different between treated mice and controls. This suggests that the action of Ts29.2 is linked neither to cellular toxicity nor to the inhibition of the previously reported angiogenic properties of Co-029/tspan8. An inhibition of cell proliferation in vivo is demonstrated by a reduction of the mitotic index in HT29 tumors of Ts29.2 treated mice. The discrepancy between in vitro and in vivo data on cell proliferation suggests that the binding of Ts29.2 to tumour cells may modify their response to signals issued from the microenvironment. Given the restricted pattern of tissue expression of the tetraspanin Co-029/tspan8, these preliminary results put forth for consideration the antibody targeting of this tetraspanin in further investigations for therapeutic applications.